Financial Management Training to Improve MSME Business Efficiency in the Skip Medan Area - Yonson Pane; Deliyanti Simbolon (Outline Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in the Medan Skip area, still face various challenges in managing their business finances effectively and efficiently. Problems such as mixing personal and business finances, not recording daily transactions, and not knowing how to prepare simple financial reports are major obstacles to their business development. This community service activity aims to improve the financial management capacity of MSMEs through intensive training and direct field mentoring. The methods used in this activity included identifying training needs, developing participatory training modules, implementing three days of interactive training, and providing one month of mentoring. Evaluation was conducted through pre- and post-tests, as well as field observations and interviews. The results of the activity showed a significant improvement in participants' understanding and practice of financial management. Approximately 78% of participants were able to prepare simple financial reports, and 84% had separated personal and business finances. Furthermore, participants became more disciplined in recording daily transactions and began implementing short-term financial planning. In conclusion, financial management training tailored to local needs and contexts can improve MSME business efficiency. This activity also encourages changes in managerial behavior and strengthens the business foundation in facing future economic challenges.